Sexual Dimorphism of Occipital Condyle of Adult Human Cranium (Bangladesh Journal of Anatomy, 2018)
Context: Measurement of occipital condyle is frequently used to calculate various dimensions which are important in anatomy, anthropology and forensic medicine as a method for determination of sex. Materials and methods: A cross-sectional analytical type of study was conducted in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from January 2013 to June 2014. A total of 100 morphologically normal complete crania was examined. The minimum and maximum distance between right and left occipital condyles and maximum bicondylar breadth between occipital condyles in male and female were measured and compared. Results: The mean minimum distance between right and left occipital condyles was 20.72 ± 2.14 mm in males and 18.41 ± 2.32mm in female.The mean maximum distance between right and left occipital condyles was 37.19 ± 4.24mm and 35.09 ± 4.37mm in male and female respectively. The mean maximum bicondylar breadth between occipital condyles was 48.62 ± 2.64 mm in male and 45.57 ± 2.67 mm in female. Conclusion: Statistically significant difference (p